Pola Asuh Keturunan Bangsawan Lalu-Baiq Budaya Lombok dalam Membentuk Karakteristik Anak melalui Layanan Bimbingan dan Konseling - Zuhdi Majdi (Universitas Kristen Satya Wacana, 2018)
Parenting is a process in the family, the interaction of parents and children. The family is where a child is born, the first place a child gets an education, consisting of father, mother and child. The family also became the main central place of character education formation of children. Family education is the fundamental or foundation of subsequent children's education. In the society of the nobility and in general people Sasak known to have the motto of Lomboq Mirah Sasak Adi meaning Lomboq straight meaning. Mirah is a true gem, an elegant precious metal that is very expensive. Sasak comes from sa'sa 'sa'i, sopo, seke' which means one. Adi means something that is very high value. Therefore, the true (mule jati) "straight road" is a very noble path, a very high value, as the only path to be followed by the sasak. and the road is a straight path (siratulmustakim) commanded by Allah SWT contained in the Qur'an and Al Hadith. In the process of learning guidance and counseling teachers are teachers who are tasked to provide guidance to students who are problematic and who are not problematic if considered important by the teacher guidance and counseling, therefore the role of teachers guidance and counseling in the learning process is needed, because learners have problems are diverse